Follicle stimulating hormone secreting pituitary adenoma: a challenging diagnosis - Mehendale, Madhuri Alap; Kalkal, Nidhi Devendra; Sarmalkar, Meenal Shailesh; Nayak, Arun Harishchandre (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
FSH secreting pituitary adenomas are relatively uncommon brain tumours and usually non-functioning. But in rare cases they produce ovarian hyperstimulation. We report a case of a 32 year old female P2L2, with amenorrhoea of 1 year, pain in abdomen and galactorrhoea since 6 months. Initially thought to be a simple prolactinoma with multicystic ovaries, but after thorough investigations to our surprise diagnosed to be a rare case of gonadotropin secreting pituitary adenoma. Patient was successfully managed by excision of the pituitary adenoma.